Energy, economic and environmental impact analysis of phase change materials for cold chain transportation in Malaysia. (1st November 2022) - Chandran, Ratanashangkari; Hasanuzzaman, M.; Arıcı, Müslüm; Kumar, Laveet
Abstract: The tropical climate of Malaysia presents higher environmental temperatures ranging from 27 to 31 °C and refrigerated semi-trailer trucks are utilized in cold chain transportation which is subjected to high thermal stresses and leads to elevated refrigeration load requirements. This subsequently causes a surge in diesel fuel consumption by the auxiliary refrigeration unit and greenhouse gas emissions into the atmosphere. To address the issue, this research evaluates the integration of phase change material (PCM) in refrigerated vehicle walls for latent heat storage purposes, which consequently reduces refrigeration load. Reference cases without PCM and 10 different PCM cases of commercially available organic-based paraffin PCM are investigated, whereby the conventional insulation method of a refrigerated semi-trailer is modified by adding a layer of PCM within its envelope, to simulate refrigeration loads during an 8-hour vehicle operational period. The PCMs are assessed based on their physicochemical properties, and performance in energy savings, economic, and environmental benefits. Results show that daily refrigeration loads can be reduced up to 34.4 % upon PCM integration in refrigerated vehicle walls, and besides, economically, the solution is highly profitable with a benefit-cost ratio above 1. The highest performing PCMs in terms of energy savings yield short payback periods of <3 years, which are at least 2.6 times lesser than the vehicle's lifetime, whilst providing greenhouse gas emission savings of above 2700 kgCO2 /year. This research indeed serves as a starting point to explore the large-scale usage of PCMs in cold chain transportation in Malaysia. Highlights: Refrigeration loads can reduce up to 34.4 % upon PCM integration in vehicle walls. PCMs based energy saving the shortest payback period is <3 years. PCM integration in vehicles can reduce GHG emissions by about 2700 kgCO2 /year.